1984
DOI: 10.1016/s0010-9452(84)80038-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Basis for the Agrammatic's Difficulty in Producing Main Verbs

Abstract: Current theories of agrammatism do not provide a clear explanation for the co-occurrence of omission of grammatical markers and main verbs in this disorder. This study tested the hypothesis that the two symptom features have distinct underlying causes. Specifically, that the omission of main verbs in agrammatic speech is caused, at least in part, by a lexical (as opposed to a syntactic) deficit. Agrammatic and anomic aphasics and normal controls were given an object and action naming test. Agrammatic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
240
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 471 publications
(256 citation statements)
references
References 5 publications
13
240
0
3
Order By: Relevance
“…If these aphasics suffer from retrieval problems for verbs, as is often suggested in the literature (e.g. Cheng & Bates, 1998;Miceli, Silveri, Villa, & Caramazza, 1984;Zingeser & Berndt, 1990), then a frequency effect might be expected. Although a frequency effect has often been shown for retrieval deficits for nouns, it has been mentioned before that such an effect for verbs does not exist (see, e.g., Jonkers, 1998).…”
Section: Discussionmentioning
confidence: 77%
“…If these aphasics suffer from retrieval problems for verbs, as is often suggested in the literature (e.g. Cheng & Bates, 1998;Miceli, Silveri, Villa, & Caramazza, 1984;Zingeser & Berndt, 1990), then a frequency effect might be expected. Although a frequency effect has often been shown for retrieval deficits for nouns, it has been mentioned before that such an effect for verbs does not exist (see, e.g., Jonkers, 1998).…”
Section: Discussionmentioning
confidence: 77%
“…As we mentioned in the Introduction, several studies in the neuropsychological literature have described patients who have greater difficulty producing verbs than nouns [4,6,9,32,35]. However, at least some of these putative verb impairments seem to be of a very different type than the deficit exhibited by R.C.…”
Section: Verb Production and Inflectional Morphologymentioning
confidence: 99%
“…1 and 2). Numerous neuropsychological [10,22,23,31,49] and neuroimaging [7,14,15,18,35] studies have implicated these regions in grammatical processing and computation of morphological agreement.…”
Section: Neuroanatomical Correlates Of Grammatical Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Verb production; Unaccusatives; Syntactic deficits; Agrammatism It has been well documented in the literature that some individuals with aphasia, particularly those showing deficit patterns consistent with a diagnosis of Broca's aphasia with agrammatism, evince greater difficulty producing verbs as compared to nouns (Berndt, Mitchum, Haendiges, & Sandson, 1997; Miceli, Silveri, Nocentini, & Caramazza, 1988;Miceli, Silveri, Villa, & Caramazza, 1984; Thompson et al, l995b;Zingeser & Berndt, 1990). While recent research focused on determining the nature of verb production deficits has shown that several factors may play a role in this production difficulty, including frequency and familiarity (Kemmerer & Tranel, 2000), imageability (Bird, Howard, & Franklin, 2000), and semantic factors (Breedin, Saffran, & Schwartz, 1998), the number of syntactic arguments associated with the verb and corresponding participant roles has been shown to influence verb production in several studies (Jonkers & Bastiaanse, 1996Kegl, 1995;Kemmerer & Tranel, 2000;Kim & Thompson, 2000;Kiss, 2000 Lange, Schneider, & Shapiro, 1997; Thompson, Shapiro, Li, & Schendel, 1995a).…”
Section: Introductionmentioning
confidence: 99%